Scar stenosis of the esophagus due to caustic corrosion. Esophagus gastrostomy high in the upper room of the esophagus also 7 years of corrosion: contribution to the prophylaxis of stenosis due to early dilatation. Pathology of corrosion and scars - Larghero Ibarz, Pedro (Cirugía del Uruguay, 2020)
Presented at session 4th April 1951